Therapy of environmental mycobacterial infections - Fabroni, Caterina; Buggiani, Gionata; Lotti, Torello (Dermatologic therapy, 2008)
Environmental mycobacteria are the causative factors of an increasing number of infections worldwide. Cutaneous infections as a result of environmental mycobacteria are often misdiagnosed, and their treatment is difficult because these agents can show in vivo and in vitro multidrug resistance. The most common environmental mycobacteria that can cause cutaneous infections are Mycobacterium fortuitum and Mycobacterium marinum. All mycobacteria are characterized by low pathogenicity and they can contaminate affected or traumatized skin only in immunocompetent subjects (mainly in fishermen, swimming‐pool attendants, and aquarium owners) whereas medical and esthetic procedures are at risk for the infections because of the quick‐growing mycobacteria. Immunocompromised subjects can instead easily develop environmental mycobacterial infections of differing degrees of severity.